The development and characterization of near-isogenic and pyramided lines carrying resistance genes to brown planthopper with the genetic background of japonica rice (Oryza sativa L.) - Nguyen, Cuong D.; Verdeprado, Holden; Zita, Demeter; Sanada-Morimura, Sachiyo; Matsumura, Masaya; Virk, Parminder S.; Brar, Darshan S.; Horgan, Finbarr G.; Yasui, Hideshi; Fujita, Daisuke (MDPI, 2019)
The brown planthopper (BPH: Nilaparvata lugens Stål.) is a major pest of rice, Oryza sativa, in Asia. Host plant resistance has tremendous potential to reduce the damage caused to rice by the planthopper. However, the effectiveness of resistance genes varies spatially and temporally according to BPH virulence. Understanding patterns in BPH virulence against resistance genes is necessary to efficiently and sustainably deploy resistant rice varieties. To survey BPH virulence patterns, seven near-isogenic lines (NILs), each with a single BPH resistance gene (BPH2-NIL, BPH3-NIL, BPH17-NIL, BPH20-NIL, BPH21-NIL, BPH32-NIL and BPH17-ptb-NIL) and fifteen pyramided lines (PYLs) carrying multiple resistance genes were developed with the genetic background of the japonica rice variety, Taichung 65 (T65), and assessed for resistance levels against two BPH populations (Hadano-66 and Koshi-2013 collected in Japan in 1966 and 2013, respectively). Many of the NILs and PYLs were resistant against the Hadano-66 population but were less effective against the Koshi-2013 population. Among PYLs, BPH20+BPH32-PYL and BPH2+BPH3+BPH17-PYL granted relatively high BPH resistance against Koshi-2013. The NILs and PYLs developed in this research will be useful to monitor BPH virulence prior to deploying resistant rice varieties and improve rice’s resistance to BPH in the context of regionally increasing levels of virulence.